IDE KESEIMBANGAN DALAM PEMBAHARUAN SISTEM PEMIDANAAN NASIONAL - Enny Patria (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2014)
The idea of balance ", which includes: monodualistik balance between the public interest (public) and individual interests (individual); balance between the protection of ideas (the interests of victims) and the idea of individualization of the criminal; balance between the elements / objective factors (physical) and subjective (inner or spiritual attitude) / idea-dader daad Strafrecht; balance between formal and substantive criteria; balance between legal certainty, flexibility / elasticity / flexibility and fairness, and balance of national values and the values of the global / universal. Policy formulation is the idea of balance in the National Criminal Justice System problem-oriented source of law (principle of legality or foundation), based on the principle of formal legality (under the Act), which became the main base, but also based on the principle of the legality of the material by giving place to the "law living in the community (the living law), but the concept is to give guidance to the extent consistent with the principles embodied in the Pancasila.